Eliminativism and Evolutionary Debunking - Jeffrey Bagwell (Ergo, An Open Access Journal of Philosophy, 2021)
Eliminativists sometimes invoke evolutionary debunking arguments against ordinary object beliefs, either to help them establish object skepticism or to soften the appeal of commonsense ontology. I argue that object debunkers face a self-defeat problem: their conclusion undermines the scientific support for one of their premises, because evolutionary biology depends on our object beliefs. Using work on reductionism and multiple realizability from the philosophy of science, I argue that it will not suffice for an eliminativist debunker to simply appeal to some object-free surrogate theory of evolution that results from converting any scientific proposition about some object K into a proposition about simples arranged K-wise. In the process, I examine some hazards peculiar to eliminative reductions of scientific theories, and propose a trilemma for eliminativists who attempt to recoup generality for ontologically sparse reducing theories by appealing to pluralities of simples arranged K-wise. The paper is intended to define and develop the object debunker’s self-defeat problem for further study, and to clarify some of the ways sparse and abundant ontologies interact with scientific theory.